THE ACTİONS THAT CAN BE TAKEN FOR BURSA AND LOCAL GOVERNMENTS WİTH REGARD TO THİRD AGE TOURİSM (Third Sector Social Economic Review, 2023)
Concerns on the worldwide consequences of the population’s aging increases gradually. This fact, much more affecting the developed countries previously has now taken hold of the developing countries as well. Creating complete policies including various disciplines such as economics, architecture, medicine and sociology was made unavoidable with the aging of the population. Moreover, the happiness of the old population which is the majority of the country’s population is important in terms of increasing the welfare of the public. Developed countries focus on increasing the quality of life and developing active aging strategies in order to succeed in quality and variety of the policies for old people. The ever increasing life standards in today’s world has increased old people’s desires, demands and expectations just like every segment of society. At this point, third age tourism expressing the travels of the people principally above 50 in general to the places out of their residences and the places they meet their needs gained importance. In this study, the advantages and the disadvantages of Bursa city with regards to third age tourism will be discussed and the actions that can be taken by the local governments for the development of third age tourism in Bursa will be reviewed. The ultimate aim of the study is to evaluate the tourism potential of Bursa city in terms of the elderly and to emphasize the contributions that third age tourism can offer to the development of the city. Because Bursa; It is among the prominent cities of Turkey in terms of third age tourism with its historical texture, natural beauties, healing water resources, health potential, rich cuisine and transportation opportunities.
Keywords: Third age tourism in Turkey; old people tourism; local governments